Systematic literature review of conversational code-switching in multilingual society from a sociolinguistic perspective - Zhong, Xinyi; Ang, Lay Hoon; Sharmini, Sharon (Academy Publication, 2023)
Code-switching (CS) is widely used across the globe despite the unclear research trends and gaps in CS studies due to under-researched reviews on it. The current study is a systematic literature review (SLR) of conversational CS from a sociolinguistic perspective from 2010 to 2022 using the PRISMA 2020 framework. Keywords query was performed at Oct 31, 2022 on Scopus and Web of Science databases. As a result, a total of 117 articles were included for further analysis. It is found that the number of CS studies was continuously increasing before encountering declines from 2019. Previously, scholars preferred empirical studies, qualitative designs, and data collection methods including discourse analysis, observation, interview and questionnaire. Regarding research objectives, a majority of studies examined the factor of CS, mainly from the micro levels. Besides that, many studies had explored attitude and identity towards CS in the past five years. As for research contexts, Asia became the research centre of previous CS studies. However, there was a lack of CS studies worldwide, especially among Oceania, South America and Africa. Multilingual societies in the Expanding Circle require more discussion.